2015
DOI: 10.1007/698_2015_363
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Technologies for Wastewater Reuse: Fate of Contaminants of Emerging Concern

Abstract: The presence of thousands of microcontaminants in wastewaters and their potential risks has drawn a large attention of the scientific community during the last years. The presence of these contaminants is especially controversial when wastewater is considered for reuse because a large number of microcontaminants are frequently not totally removed by conventional wastewater treatment processes. As a contribution to the knowledge in this field, this chapter focuses on the application of four well-known and widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
0
27
0
1
Order By: Relevance
“…Although this is potentially a major advantage for wastewater treatment sustainability, introducing the idea of AnMBR effluent recycling also brings about additional concerns regarding the impacts of emerging contaminants (i.e., organic micropollutants, antibioticresistant pathogens, antibiotic resistance genes etc.) on the environments exposed to irrigation [6][7][8]. …”
Section: The Anaerobic Mbr As An Alternative To Conventional Wastewatmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is potentially a major advantage for wastewater treatment sustainability, introducing the idea of AnMBR effluent recycling also brings about additional concerns regarding the impacts of emerging contaminants (i.e., organic micropollutants, antibioticresistant pathogens, antibiotic resistance genes etc.) on the environments exposed to irrigation [6][7][8]. …”
Section: The Anaerobic Mbr As An Alternative To Conventional Wastewatmentioning
confidence: 99%
“…However, the current state of conventional wastewater treatment does not sufficiently address the concerns arising from emerging contaminants in agricultural and municipal wastewaters to allow for direct reuse in most instances [7]. Furthermore, microbial safety is at the forefront of the emerging concerns associated with wastewater reuse and is directly linked to non-microbial issues such as antibiotic presence and formation of DBPs [138,139].…”
Section: Wastewater Treatment Sustainability: the Role Of Anmbrs In Rmentioning
confidence: 99%
“…Regenerated wastewater usage in agriculture is a widespread practice in countries that face water scarcity, because it is a feasible solution to save and manage the available water resources [2]. However, the increasing presence of micropollutants in wastewater is a relevant impediment for this practice, as they accumulate on the plantations, on the soil, and they can even reach the groundwater by percolation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to membrane filtration, ozonation cannot remove LMWS but can serve as a technique for brine recovery from wastewater. Ozone oxidation can give good results when many poorly degradable contaminants, including textile dyes, are taken into consideration [9,10]. It can be concluded that the effectiveness of dye decomposition by ozone treatment has been proven in many papers, and the field seems to be well covered by the literature (Table 1).…”
mentioning
confidence: 99%
“…Another problem is the huge volume of highly contaminated concentrate and backwashes. At present, the operating cost of membrane filtration is still high when industrial wastewater treatment is concerned [9].An application of ozone as a non-discharge treatment method can be an alternative for the purification of textile wastewater contaminated by LMWS. In contrast to membrane filtration, ozonation cannot remove LMWS but can serve as a technique for brine recovery from wastewater.…”
mentioning
confidence: 99%